Identification of prognostic and cellular senescence gene E2F1 of papillary thyroid carcinoma through bioinformatics analyses and experimental verification - Yu, Bin; Zhao, Shu-Yan; Zhu, Yun-Hua; Luo, Jun-Jie; Zheng, Ke; Shen, Bin-Jie; Shen, Yi-Lin; Zhong, Huan-Xin (Frontiers in Genetics, 2025)
ObjectiveThis work aimed to find a new prognostic cell senescence gene to predict the prognosis of patients with papillary thyroid carcinoma (PTC).MethodsThe data of the patients with PTC were collected from the Cancer Genome Atlas (TCGA) database. The gene set of cellular senescence was collected from the website of CellAge. The function of hub genes was analyzed by various bioinformatics methods including expression analysis, survival analysis, and nomogram analyses. Real-time quantitative PCR, cell transfection, colony formation assay, Western blot, wound healing assay, transwell assay, cell counting Kit-8, flow cytometry, and immunohistochemistry staining were performed to verify the function of hub gene.ResultsE2F1 was finally screened as the key senescence gene, and its expression was higher in PTC tumors than in normal. KM curve indicated that PTC patients with higher expression of the E2F1 had longer survival times. The GSEA showed that the high expression group of E2F1 was enriched in DNA replication and so on. Cell experiments showed that overexpression of E2F1 significantly increased relative protein expression of senescence related markers, including p21, p53, γ-H2AX, and p16INK4a. Cell experiments also showed that overexpression of E2F1 inhibited the invasion, proliferation, and migration of tumor cells. While knockdown of E2F1 reversed these results.ConclusionE2F1 was found to be upregulated in PTC, with its high expression significantly correlated to a favorable patient prognosis. E2F1 suppresses malignant tumor phenotypes by modulating cellular senescence. A predictive model integrating E2F1 and clinical features accurately forecasts poor prognosis, indicating E2F1’s potential as a therapeutic target for PTC.